Maggie Black: The Medieval Cookbook - Mason, Laura (Petits Propos Culinaires, 1992)
Maggie Black: The Medieval Cookbook: British Museum Press, London, 1992: 143 pp, lavishly illustrated, bibliography, £14.95.